2017
DOI: 10.1371/journal.pone.0180017
|View full text |Cite
|
Sign up to set email alerts
|

Contingent association between the size of the social support network and osteoporosis among Korean elderly women

Abstract: ObjectiveTo investigate the association between the number of personal ties (or the size of the social support network) and the incidence of osteoporosis among older women in Korea.MethodsData from the Korean Urban Rural Elderly Study were used. Bone density was measured by dual-energy X-ray absorptiometry at the lumbar spine (L1–L4) and femur neck. T-score, the standardized bone density compared with what is normally expected in a healthy young adult, was measured and the presence of osteoporosis was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In this study, bone density in those without social participation was significantly lower than in those with social participation, a finding consistent with previous studies such as Lee et al, which indicated that a lack of social relationships increases the risk of osteoporosis [26]. A harmful lifestyle, such as having an inadequate dietary intake of calcium, vitamin D, and protein; physical inactivity; smoking; and lower estrogen secretions, especially after menopause, are known to be risk factors for bone-related issues [27][28][29].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, bone density in those without social participation was significantly lower than in those with social participation, a finding consistent with previous studies such as Lee et al, which indicated that a lack of social relationships increases the risk of osteoporosis [26]. A harmful lifestyle, such as having an inadequate dietary intake of calcium, vitamin D, and protein; physical inactivity; smoking; and lower estrogen secretions, especially after menopause, are known to be risk factors for bone-related issues [27][28][29].…”
Section: Discussionsupporting
confidence: 92%
“…Because participating in hobby clubs is about doing what one loves, frequent participation in hobby clubs is quite unlikely to place psychological stress on participants. Furthermore, women are more sensitive to closeness with the members of their network than men, and the intimacy of human relationships has a greater effect on health for women than for men [45,46]. Because members of hobby clubs share a common interest, they are more likely to open up to one another and achieve an intimate relationship than those involved in other types of SP.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that social support when was manageable in size decreased rates of stress and depression, both factors associated to bone loss. 65 Furthermore, a large longitudinal study in a Southern European population studied the incidence rate and risk factors for hip fracture, both in males and females. They observed a higher proportion of illiteracy and depression with a significantly greater hip fracture rate in females than in males.…”
Section: Sociocultural Gender As Mediator and Modifier Of Bone Health...mentioning
confidence: 99%